MEMBANGUN SISTEM PEMETAAN DARI UDARA BERBIAYA RENDAH DENGAN WAHANA UDARA NIR-AWAK MINI - Rokhmana, Catur Aries (Badan Informasi Geospasial in Partnership with MAPIN, 2010)
The production for 1/1.000 -1/2.500 scale maps are still done by the aerial photography or survey methods terrestrial which are not cheap. This paper describes an alternative aerial mapping system which is relatively less expensive to produce large scale maps (1/1.000 - 1/5.000) using unmanned aerial vehicle (UAV). For keeping the lowest cost, the instrumentation build from the stuff that exist in the market such as aeromodeling and digital cameras. For supporting the operational of this system, the database of Indonesian territory was build also. This system consists of several modules namely (1) air vehicle, (2) imaging sensors and the stand, (3) data processing and visualization of results; (4) ground station, and (5) database. This system has been tested to produce the photomaps scale 1/2.500. Geometric quality improvements made possible by conducting the process of camera calibration with